Biosynthetic and environmental effects on the stable carbon isotopic compositions of anteiso- (3-methyl) and iso- (2-methyl) alkanes in tobacco leaves - Grice, Kliti; Lu, H.; Youping , Z.; Stuart-Williams, H.; Farquhar, G. (Elsevier, 2008)
Abstract available as a pdf file in full text field